226k views
4 votes
Given g(x) = x squared - x, find g (2/3)

2 Answers

6 votes

Answer:


\large\boxed{g\left((2)/(3)\right)=-(2)/(9)}

Explanation:


g(x)=x^2-x=x(x-1)\\\\g\left((2)/(3)\right)\to\text{put }\ x=(2)/(3)\ \text{to the eqation of the function:}\\\\g\left((2)/(3)\right)=\left((2)/(3)\right)\left((2)/(3)-1\right)=\left((2)/(3)\right)\left((2)/(3)-(3)/(3)\right)=\left((2)/(3)\right)\left(-(1)/(3)\right)=-((2)(1))/((3)(3))=-(2)/(9)

User Chungzuwalla
by
5.1k points
2 votes

Answer:

-2/9

Explanation:

g(x) = x^2 -x

Let x = 2/3

g(2/3) = (2/3) ^2 - 2/3

= 4/9 - 2/3

We need a common denominator of 9

4/9 - 2/3*3/3

4/9 - 6/9

-2/9

User Drahakar
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.